2013
DOI: 10.3402/snp.v3i0.20767
|View full text |Cite
|
Sign up to set email alerts
|

Pornography addiction – a supranormal stimulus considered in the context of neuroplasticity

Abstract: Addiction has been a divisive term when applied to various compulsive sexual behaviors (CSBs), including obsessive use of pornography. Despite a growing acceptance of the existence of natural or process addictions based on an increased understanding of the function of the mesolimbic dopaminergic reward systems, there has been a reticence to label CSBs as potentially addictive. While pathological gambling (PG) and obesity have received greater attention in functional and behavioral studies, evidence increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 69 publications
1
40
0
3
Order By: Relevance
“…Many researchers, however, have posited that sexual addiction most clearly captures the nature of out of control sexual behavior (Carnes, 2001;Garcia & Thibaut, 2010;Goodman, 2001;Hagedorn & Juhnke, 2005;Samenow, 2010) with neuroscience scholars and researchers supporting this assertion (Hilton, 2013;Kühn & Gallinat, 2014;Voon et al, 2014). Carnes (2001) described sexual addiction as an unhealthy relationship with a "mood-altering experience" (p. 14), suggesting that sex addiction is not about frequency or type of sexual behavior, but rather about a pathological relationship with sexual behaviors that are uncontrollable and persist regardless of harmful consequences.…”
mentioning
confidence: 99%
“…Many researchers, however, have posited that sexual addiction most clearly captures the nature of out of control sexual behavior (Carnes, 2001;Garcia & Thibaut, 2010;Goodman, 2001;Hagedorn & Juhnke, 2005;Samenow, 2010) with neuroscience scholars and researchers supporting this assertion (Hilton, 2013;Kühn & Gallinat, 2014;Voon et al, 2014). Carnes (2001) described sexual addiction as an unhealthy relationship with a "mood-altering experience" (p. 14), suggesting that sex addiction is not about frequency or type of sexual behavior, but rather about a pathological relationship with sexual behaviors that are uncontrollable and persist regardless of harmful consequences.…”
mentioning
confidence: 99%
“…This is what happened with the availability of pornography on the internet. There is strong evidence that people are becoming addicted to it (Hilton, 2013). Also here we can see how science and technology have an effect on the experience of our sexuality.…”
Section: Science and Visibilitymentioning
confidence: 93%
“…Pornography on the internet with its easy access, availability and anonymity has raised concerns about its effects on sexual behaviors and brain development [58], its positive correlation with aggressive behavior, particular among high-risk males [65], and marital infidelity [66]. The potential of pornography to amplify the brain's addiction-related neuroplasticity by an accelerated novelty 'supranormal stimulus' effect has been put forth [57].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been suggested that pornography has the potential to alter brain structures permanently, with the developing brain being the most vulnerable [57,58]. Because of current inconsistent neurobiological findings linking sexual images and behaviors with brain activity, more research in this area is needed [17,59].…”
Section: Discussionmentioning
confidence: 99%